The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1186/s12884-023-05692-5
|View full text |Cite
|
Sign up to set email alerts
|

Measuring resilience and stress during pregnancy and its relation to vulnerability and pregnancy outcomes in a nulliparous cohort study

Abstract: Background Resilience reflects coping with pregnancy-specific stress, including physiological adaptations of the maternal organism or factors arising from the socioeconomic context, such as low income, domestic violence, drug and alcohol use, lack of a support network and other vulnerability characteristics. Resilience is a dynamic characteristic that should be comparatively evaluated within a specific context; its association with perceived stress and social vulnerability during pregnancy is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Indeed, the mitochondrial genome has a high rate of mutagenesis due to its exposure to external and internal noxious stimuli (Alexeyev et al, 2013). This leads to frequent mutations that may affect mtDNA stability and confer susceptibility to further challenges such as chronic stress (Bobba- Alves et al, 2023). Additionally, while genetic association studies in PPD are scarce, a few notable associations have been identified with mitochondrial interactors.…”
Section: Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the mitochondrial genome has a high rate of mutagenesis due to its exposure to external and internal noxious stimuli (Alexeyev et al, 2013). This leads to frequent mutations that may affect mtDNA stability and confer susceptibility to further challenges such as chronic stress (Bobba- Alves et al, 2023). Additionally, while genetic association studies in PPD are scarce, a few notable associations have been identified with mitochondrial interactors.…”
Section: Geneticsmentioning
confidence: 99%
“…Additionally, as it is difficult to tease apart pre-disposing resilience factors from passive resilience (i.e., where "resilience" is due to a lack of a marker in susceptible subjects, such as nutrient deficiency) (Pfau and Russo, 2015), the field should shift focus to understanding whether and how pre-existing individual differences play a role in resilience to PPD. Finally, as psychological and socioeconomic resilience factors are some of the most studied in the clinical setting (Julian et al, 2021;Alves et al, 2023), we must aim to better understand how these factors are related to biology, and specifically how they are related to mitochondrial function. After all, preclinical work demonstrates that mitochondria are involved in social behaviors and may be affected by social stressors (Hollis et al, 2015(Hollis et al, , 2022Ülgen et al, 2023), suggesting that these factors are intertwined with biology.…”
Section: Outstanding Questions Regarding Mitochondria In Resiliencementioning
confidence: 99%
“…), and family economic burden. 11 A study on pregnant women in northwest China showed that Among 750 respondents, 709 (94.53%) had mild or above pregnancy stress. 12 The ACE (Anonymity, Convenience, and Escape) theoretical model proposed by Young 13 illustrated that the network had the characteristic of avoidance, and individuals used the network to escape the pressure generated in life.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have begun to explore the relationship between these personality traits and postpartum mental health [18,19]. For example, women scoring higher in neuroticism have been reported to experience more severe symptoms of PPD [20].…”
Section: Introductionmentioning
confidence: 99%